Проблеми формування міграційної політики України в сучасних умовах - Позняк, О.В. (Інститут демографії та соціальних досліджень НАН України, 2009)
В статье рассматриваются проблемы формирования миграционной политики Украины в новых макроэкономических и геополитических реалиях. Обосновывается необходимость либерализации миграционной политики, предложена система приоритетов привлечения мигрантов. Разработаны принципы дифференцированного подхода к регулированию трудовых миграций. In the article are presented results of action a new migratory policy of the Russian Federation within the first year after its introduction. It is emphasized, that the society is not ready to accept the liberal policy . It is shown, that results of action of new policy give the full bases to speak about impression positive effect. Offers on updating the new legislation is analyzing.